Restorative Justice Efforts in Resolving Domestic Violence Crimes from the Perspective of Positive Law and Islamic Law - Kholid, Muhamad; Achmad; Leliya (Journal of Islamic Communication and Counseling, 2026)
The phenomenon of domestic violence (KDRT) in Indonesia remains a serious issue that impacts the psychological, social, and human rights aspects of victims. Through a restorative justice approach and normative analysis of positive law and Islamic law, this study aims to evaluate the effectiveness of restorative approaches in resolving domestic violence cases. The research employs a qualitative method with data collection techniques including literature review, legal document analysis, and interviews with relevant stakeholders. The findings indicate that the restorative justice approach holds strong relevance both from the perspective of positive law, as regulated in Law No. 23 of 2004 on the Elimination of Domestic Violence and Indonesian National Police Regulation No. 8 of 2021, and from the perspective of Islamic law, which emphasizes the principles of ishlah (reconciliation) and sulh (peaceful settlement). This approach aligns with efforts to restore victims (ḥifẓ al-nafs) and maintain family harmony (ḥifẓ al-usrah). However, its implementation faces challenges such as patriarchal cultural resistance, inadequate mediation infrastructure, and lack of coordination between law enforcement agencies and religious leaders. This study concludes that integrating restorative justice approaches based on positive law and Islamic legal principles can create a more holistic and equitable model for resolving domestic violence cases. Policy recommendations include strengthening mediator capacity, developing integrative guidelines, and enhancing collaboration between the government and religious communities.